Multiple-loudspeaker systems - Krzysztof RUDNO-RUDZIŃSKI (Archives of Acoustics, 2016)
In this paper it is shown that a multiple-loudspeaker system composed of N similar loudspeakers can be replaced by N independent, similar single-loudspeaker systems. This provides the possibility of applying known methods of analysis and synthesis to multiple-loudspeaker systems. The efficiency of the multiple-loudspeaker system is calculated and measured results of the efficiency are given. Standardized transmittance functions for multiple-loudspeaker systems are discussed. The resonance frequencies of multiple-loudspeaker systems are determined.